Characterization and functional analysis of a caspase 3 gene: Evidence that ChCas 3 participates in the regulation of apoptosis in Crassostrea hongkongensis. Issue 98 (March 2020) - Qin, Yanping; Zhang, Yuehuan; Li, Xingyou; Noor, Zohaib; Li, Jun; Zhou, Zihua; Xu, Duo; Zhao, Zehui; Xiang, Zhiming; Yu, Ziniu
Abstract: Caspase 3 plays an important role in apoptotic pathways and contributes to maintaining the homeostasis of the immune system in organisms. The structure, functions, and characteristics of caspase 3 have been extensively investigated in many species, but the research is scarce when it comes to bivalves, particularly oysters. In this study, we identified and cloned a previously unknown caspase 3 gene, named Ch Cas 3, in C. hongkongensis . The full-length cDNA of Ch Cas 3 was 1562 bp and included a 175 bp 5′-untranslated region (UTR), a 141 bp 3′-UTR and a 1245 bp open reading frame (ORF) that encoded a polypeptide of 415 amino acids. Similar to caspase 3 in other species, Ch Cas 3 has a pro-domain, a conserved cysteine active site, a large p20 subunit and a small p10 subunit. Our findings demonstrated the expression of Ch Cas 3 in all the eight tissues via tissue-specific expression assays with the highest expression in haemocytes. Ch Cas 3 was confirmed to be expressed throughout the larval development stages, and fluorescence from pEGFP-N1- Ch Cas 3 was found to be distributed throughout the entire HEK293T cell. In addition, the relative expression of Ch Cas 3 significantly enhanced in hemocytes post bacterial stimulation, and overexpression of Ch Cas 3 led to upregulation of the transcriptional activity of NF-κB and p53 reporter genes in HEK293T cells, which indicated that it was involved in innate immune responses. Finally, the apoptosis rate of the haemocytes declined considerably compared with that of the control group after the expression of Ch Cas 3 was successfully silenced by dsRNA, corroborating its sentinel role in apoptosis. This study provides comprehensive underpinning evidences, affirming caspase 3 crucial role against bacterial infection and apoptosis in C. hongkongensis . Highlights: Ch Cas 3 was identified from Crassostrea hongkongensis with a full length of 1562 bp. Ch Cas 3 mRNA expressions was significantly increased after bacterial stimulation. Over-expression of Ch Cas 3 could improve the transcriptional activity of NF-κB and p53. Successful silencing of Ch Cas 3 could significantly reduce the apoptosis rate.